Four‐Year‐Old Children's Negotiation Strategies to Influence and Deal with a Primary Child Health Care Situation. (5th April 2011) - Harder, Maria; Christensson, Kyllike; Söderbäck, Maja
Abstract : In Sweden, children's health and development are promoted through Primary Child Health Care (PCHC) visits. The children participate in these visits from their own perspective through bodily and verbal expressions. This study explores four‐year‐old children's expressions when they as actors take part in a PCHC situation. The conceptualisation of the children's expressions reveals various actions that exhibit their affirmative and delaying negotiation strategies to influence and deal with these situations. For PCHC nurses, these findings may encourage to view children as negotiating participants and inspire to sensitivity when inviting children and guiding them through health visits. © 2011 The Author(s). Children & Society © 2011 National Children's Bureau and Blackwell Publishing Limited